Phage-Derived Depolymerase as an Antibiotic Adjuvant Against Multidrug-Resistant Acinetobacter baumannii - Chen, Xi; Liu, Miao; Zhang, Pengfei; Xu, Miao; Yuan, Weihao; Bian, Liming; Liu, Yannan; Xia, Jiang; Leung, Sharon S. Y. (Frontiers in Microbiology, 2022)
Bacteriophage-encoded depolymerases are responsible for degrading capsular polysaccharides (CPS), lipopolysaccharides (LPS), and exopolysaccharides (EPS) of the host bacteria during phage invasion. They have been considered as promising antivirulence agents in controlling bacterial infections, including those caused by multidrug-resistant (MDR) bacteria. This feature inspires hope of utilizing these enzymes to disarm the polysaccharide capsid of the bacterial cells, which then strengthens the action of antibiotics. Here we have identified, cloned, and expressed a depolymerase Dpo71 from a bacteriophage specific for the gram-negative bacterium Acinetobacter baumannii in a heterologous host E. coli. Dpo71 sensitizes the MDR A. baumannii to the host immune attack, and also acts as an adjuvant to assist or boost the action of antibiotics, for example colistin. Specifically, Dpo71 at 10 µg/ml enables a complete bacterial eradication by human serum at 50% volume ratio. A mechanistic study shows that the enhanced bactericidal effect of colistin is attributed to the improved outer membrane destabilization capacity and binding rate to bacteria after stripping off the bacterial capsule by Dpo71. Dpo71 inhibits biofilm formation and disrupts the pre-formed biofilm. Combination of Dpo71 could significantly enhance the antibiofilm activity of colistin and improve the survival rate of A. baumannii infected Galleria mellonella. Dpo71 retains the strain-specificity of the parent phage from which Dpo71 is derived: the phage-sensitive A. baumannii strains respond to Dpo71 treatment, whereas the phage-insensitive strains do not. In summary, our work demonstrates the feasibility of using recombinant depolymerases as an antibiotic adjuvant to supplement the development of new antibacterials and to battle against MDR pathogens.